Controllability of Abstract Systems of Fractional Order - Henriquez-Miranda, H; Mur-Voigt, T (Walter de Gruyter GmbH, 2015)
In this paper we are concerned with the controllability of control systems governed by a fractional differential equation in Banach spaces. Using the properties of the Mittag-Leffler function we generalize to these systems a result of Korobov and Rabakh, which was established for first order systems. We apply our results to study the controllability of a system modeled by a fractional integral equation in a Hilbert space. © 2015 Diogenes Co., Sofia.